2022
DOI: 10.3390/su14074296
|View full text |Cite
|
Sign up to set email alerts
|

Human Systematic Innovation Helix: Knowledge Management, Emotional Intelligence and Entrepreneurial Competency

Abstract: This study analyzes the relationship between the innovation capacity of Spanish companies through the ability to obtain their information through the integration of these three variables: knowledge management, emotional intelligence, and entrepreneurial competency of Spanish executives. The questionnaires were distributed to executives of companies from different sectors of activity. The sample consists of 241 executives. The hypothesis was examined by structural equation modeling. Regarding the direct effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Scholarly research has found that companies embedded in automotive industrial clusters can enhance their innovation ability by strengthening knowledge management, influencing innovation performance [65]. Executives of companies can catalyze innovation through knowledge management, positively promoting enterprise innovation [66].…”
Section: Knowledge Management and Innovation Abilitymentioning
confidence: 99%
“…Scholarly research has found that companies embedded in automotive industrial clusters can enhance their innovation ability by strengthening knowledge management, influencing innovation performance [65]. Executives of companies can catalyze innovation through knowledge management, positively promoting enterprise innovation [66].…”
Section: Knowledge Management and Innovation Abilitymentioning
confidence: 99%
“…Developing entrepreneurial competencies is considered a crucial step in preparedness for self-employment. Entrepreneurial competencies are defined as the underlying characteristics such as traits, specific knowledge, skills and self-images that lead to the birth of a new venture, its survival and growth (Bl azquez Puerta et al, 2022). According to the RBV, value creation is strictly related to the competencies of managers in acquiring and developing resources.…”
Section: Literature Review 21 Theoretical Foundation -Resource-based ...mentioning
confidence: 99%
“…Teacher emotional intelligence plays a good role in building positive teacher-student relationships, and the literature [12] concluded that teachers' emotional intelligence is better handled and teachers show better discipline management in the classroom by analyzing the relationship between discipline management, gender, academic form, teacher service time, and emotional intelligence. The literature [13] analyzed three variables, such as knowledge management, emotional management, and entrepreneurship in Spain, and tested that emotional management positively affects innovation in Spanish companies using structural equation modeling.…”
Section: Introductionmentioning
confidence: 99%